A COMPREHENSIVE RESEARCH ON THE IMPACT OF MEDICINAL PLANTS FOR DEVELOPING IMMUNOTHERAPY FOR CANCER CELLS - 1. Monali Badshah Shinde , 2. Prof. (Dr.) S. B. Sahu (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
(Immunotherapy has emerged as a transformative approach in cancer treatment by harnessing the body’s immune system to combat malignant cells. While synthetic drugs dominate this field, interest is growing in bioactive compounds from medicinal plants as novel immune-stimulating agents. This research explores the pharmacological potential of key medicinal plants such as Withania somnifera, Tinospora cordifolia, Curcuma longa, and Ganoderma lucidum in enhancing immune response and inducing apoptosis in cancer cells. The study includes extraction methods, molecular pathways, in-vitro evidence, and a comparative analysis of immune-modulating effects. It concludes with a proposed pathway for developing plant-based immunotherapy drugs, making cancer treatment safer and more accessible.)